1989
DOI: 10.1346/ccmn.1989.0370507
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dry Grinding and Leaching on the Crystal Structure of Chrysotile

Abstract: Abstract--The structural damage produced by dry grinding and acid leaching of chrysotile was studied by transmission and scanning electron microscopy, infrared spectroscopy, X-ray powder diffraction, and thermogravimetric analysis. Severe dry grinding converted the chrysotile fibers into fragments having strong potential basic reaction sites. These sites were immediately neutralized by molecules present in the atmosphere (e.g., H20, CO2). Acid leaching transformed the chrysotile fibers into very porous, noncry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
0
2

Year Published

1991
1991
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(58 citation statements)
references
References 17 publications
4
52
0
2
Order By: Relevance
“…The DRIFTS absorption bands at 3000-3500 cmand at 1635 cm -x are attributed to the stretching and bending vibration of water and are especially strong for $3 and $4, which implies that water is bound to silica in the chrysotile structure (Suquet, 1989). The absorption bands are especially strong in 100% leached samples and assigned to water adsorbed on Si-OH groups.…”
Section: Generalmentioning
confidence: 95%
“…The DRIFTS absorption bands at 3000-3500 cmand at 1635 cm -x are attributed to the stretching and bending vibration of water and are especially strong for $3 and $4, which implies that water is bound to silica in the chrysotile structure (Suquet, 1989). The absorption bands are especially strong in 100% leached samples and assigned to water adsorbed on Si-OH groups.…”
Section: Generalmentioning
confidence: 95%
“…The L1 spectrum is similar to that of a pure silica sample such as Aerosil 380. As shown by Suquet (1989), IR spectroscopy is a very sensitive method for detecting the destruction of the crystalline structure of silicates whether by grinding or leaching.…”
Section: Ir Spectroscopymentioning
confidence: 99%
“…In particular, mechano-chemical treatment, which could be used for disposing of and/or recycling asbestos, is capable of increasing particle reactivity [33], reducing the sintering temperature [34] and reducing the thermal decomposition temperature [35,36]. In this regard, Suquet [37] has shown that grinding and/or leaching pre-treatment of chrysotile affected its dissolution in water. A mechano-chemical treatment was also successfully applied to asbestos by Plescia et al [38], who showed how grinding can completely modify the fibrous morphology of asbestos.…”
Section: Introductionmentioning
confidence: 99%